Religiosity and family resilience who perform Rambu Solo’ Ritual in Toraja - Pongdatu, Laurenzia Putri Salo; Huwae, Arthur (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
Rambu Solo’ is one of the customs that the Toraja people still preserve. The implementation of Rambu Solo’ becomes a challenge for some families because this ritual becomes an obligation done as a form of gratitude to people who have died. Besides that, Rambu Solo’s ceremony requires every family to be able to pay off their debt (indan) from the ritual. This problem makes the family depressed, so it is expected that the family can be resilient in daily life. Thus, This study aims to find out the relationship between religiosity and the family resilience of those who carry out Rambu Solo’s ritual in Toraja. The method used is quantitatively correlational. Participants involved as many as 93 Toraja people aged 22-50 years who had or were carrying out Rambu Solo’ ritual using incidental sampling techniques. The measurement scale uses the religiosity scale and the family resilience scale. The results showed a significant positive relationship between religiosity and the family resilience of those who perform Rambu Solo’ ritual in Toraja. This result has implications that families among Toraja who have the debt (Indan) due to carrying out Rambu Solo’ ritual, can survive after getting out of the pressure by paying off their debt (Indan).